Global governance and the international law of the sea : the evolution and practice of the continental shelf regime - Friedman, Shani (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book conducts an examination of the international legal regime of the continental shelf through the lens of international relations (IR), with a primary focus on global governance theory. Presenting a new perspective within the field of IR and international law, the book offers new insights into the rules, principles, practices, and actors that establish and govern social interactions and the management of common affairs at the transnational level. The governance framework within the continental shelf can encompass a wider scope than legal laws alone, incorporating informal rules or potentially disregarding formal "black letter" rules that may not be effectively applied in practice. To exemplify how governance theory and other IR theories contribute to the analysis of the legal regime concerning the continental shelf, the book conducts an in-depth examination of three significant issues: (i) the demarcation and delimitation of the continental shelf; (ii) the rights and obligations of coastal states in the continental shelf; and (iii) procedural matters related to the continental shelf and international maritime adjudication. This book will be of interest to students and scholars in the field of the law of the sea, international law, global governance and international relations"--
Global governance and international relations theories -- Demarcation and delimitation of the continental shelf -- The rights and obligations of coastal states in the continental shelf -- Procedural issues concerning the continental shelf.
Keywords: Continental shelf -- Law and legislation; Coastal zone management -- Law and legislation; Territorial waters; Law of the sea; LAW / Maritime; LAW / International; LAW / Environmental